Fitness & Sports Medicine - Fleckenstein D; Ueberschär O; Wüstenfeld JC; Wolfarth B (Deutsche Zeitschrift für Sportmedizin)
Aim: The aim of the present study was to investigate the reactions of oxygen consumption (VO2), heart rate (HR) and lactate accumulation (La) when running on lower body positive pressure treadmills (LBPPT).Methods: 15 well-trained male athletes (VO2peak: 60.23.8ml kg-1 min-1) completed in randomized order three analogous maximal incremental treadmill tests,recording spiroergometrical data using breath-by-breath analysis. Two tests were held on a LBPPT, with 80% and 60% body weight (80% BWSet and 60% BWSet), respectively. The third test was completed on a conventional treadmill (100% BWSet).Results: Average of all running speed stages from 10 to 18 kmh-1, VO2 decreased significantly from 48.18.4 via 39.76.8 to 33.57.3ml kg-1 min-1 at 100%, 80% and 60% BWSet (p<0.001). HR was on average 15 bpm and 27 bpm lower at 80% and 60% BWSetcompared to 100% BWSet (p<0.001), while La decreased from 2.52.3 via 1.51.1 to 1.10.5 mmol l-1 (p<0.001). Conclusion: VO2, HR and La are clearly changed by LBPPT running. Furthermore, regression analyses showed that training at a fixed VO2stimulus leads to higher lactate values on the LBPPT compared to the conventional treadmill, which may indicate a change in energy contributions.KEY WORDS: AlterG, Hypogravity, LBPPT, Anti-Gravity, Oxygen Consumption